2021
DOI: 10.3390/biomedicines9040383
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 and Intestinal Diseases

Abstract: Accumulating evidence implicates glucagon-like peptide-1 (GLP-1) to have, beyond glucose maintenance, a beneficial role in the gastrointestinal tract. Here, we review emerging data investigating GLP-1 as a novel treatment for intestinal diseases, including inflammatory bowel diseases, short-bowel syndrome, intestinal toxicities and coeliac disease. Possible beneficial mechanisms for these diseases include GLP-1′s influence on gastric emptying, its anti-inflammatory properties and its intestinotrophic effect. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 93 publications
1
27
0
1
Order By: Relevance
“…This likely results from enhanced nutrient and water absorption in the remnant intestine. The two major mechanisms for such increased absorption are likely prolonged epithelial contact time, largely mediated by the GLP‐1 effect, and increased epithelial mass, largely mediated by the GLP‐2 effect 14,31 . However, experimental evidence that an increased epithelial mass directly translates into increased epithelial function is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This likely results from enhanced nutrient and water absorption in the remnant intestine. The two major mechanisms for such increased absorption are likely prolonged epithelial contact time, largely mediated by the GLP‐1 effect, and increased epithelial mass, largely mediated by the GLP‐2 effect 14,31 . However, experimental evidence that an increased epithelial mass directly translates into increased epithelial function is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the use of GLP-1 as a possible treatment of chemotherapy-induced mucositis ( 13 , 18 ). Administration of GLP-1 analogs in mice treated with chemotherapy ameliorated mucositis and accelerated healing of the intestinal injury ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased secretion of GLP-1 is seen after chemotherapy-induced intestinal injury in rodents ( 13 , 14 ), and elevated plasma levels are observed in humans after chemotherapy ( 15 ) and during gut ischemia ( 16 ). Indeed, GLP-1 has intestinotrophic effects sustaining the integrity of intestinal mucosal barrier in animal studies ( 17 , 18 ). Administration of GLP-1 analogs can ameliorate chemotherapy-induced intestinal injury ( 13 ), while ablation of L-cells in mice has led to severe mucositis as well as insufficient intestinal healing after chemotherapy ( 14 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Агонисты рецепторов ГПП-1 с успехом применяют и при диабетической нефропатии (ДНП) для улучшения сердечно-сосудистого и почечного прогноза [7,12,15]. Имеются данные об их благоприятных эффектах на клинические проявления поражения кишечника, сопут- ствующего СД 2 типа [17]. До настоящего времени нет доказательств наличия у агонистов рецепторов ГПП-1 отчетливых протективных эффектов в отношении диабетической ретинопатии, периферической и вегетативной нейропатии, периферических сосудистых нарушений (диабетическая стопа) [1,15].…”
Section: агониCты рецепторов глюкагоноподобного пептида-1: возможност...unclassified